Multiple Microelectrode Recordings in STN‐DBS Surgery for Parkinson's Disease: A Randomized Study. Issue 3 (8th May 2018) - Bjerknes, Silje; Toft, Mathias; Konglund, Ane E.; Pham, Uyen; Waage, Trine Rygvold; Pedersen, Lena; Skjelland, Mona; Haraldsen, Ira; Andersson, Stein; Dietrichs, Espen; Skogseid, Inger Marie
Abstract: Background: Subthalamic nucleus deep brain stimulation improves motor symptoms and fluctuations in advanced Parkinson's disease, but the degree of clinical improvement depends on accurate anatomical electrode placement. Methods used to localize the sensory‐motor part of the nucleus vary substantially. Using microelectrode recordings, at least three inserted microelectrodes are needed to obtain a three‐dimensional map. Therefore, multiple simultaneously inserted microelectrodes should provide better guidance than single sequential microelectrodes. We aimed to compare the use of multiple simultaneous versus single sequential microelectrode recordings on efficacy and safety of subthalamic nucleus stimulation. Methods: Sixty patients were included in this double‐blind, randomized study, 30 in each group. Primary outcome measures were the difference from baseline to 12 months in the MDS‐UPDRS motor score (part III) in the off‐medication state and quality of life using the Parkinson's Disease Questionnaire‐39 (PDQ‐39) scores. Results: The mean reduction of the MDS‐UPDRS III off score was 35 (SD 12) in the group investigated with multiple simultaneous microelectrodes compared to 26 (SD 10) in the single sequential microelectrode group ( p = 0.004). The PDQ‐39 Summary Index did not differ between the groups, but the domain scores activities of daily living and bodily discomfort improved significantly more in the multiple microelectrodes group. The frequency of serious adverse events did not differ significantly. Conclusions: After 12 months of subthalamic nucleus stimulation, the multiple microelectrodes group had a significantly greater improvement both in MDS‐UPDRS III off score and in two PDQ‐39 domains. Our results may support the use of multiple simultaneous microelectrode recordings. Trial registration: ClinicalTrials.gov Identifier: NCT00855621 (first received March 3, 2009).